Ammonia Decomposition and Synthesis over Multinary Magnesioferrites: Promotional Effect of Ga on Fe Catalysts for the Decomposition Reaction. Issue 4 (9th February 2017) - Ortega, Klaus Friedel; Rein, Denise; Lüttmann, Christian; Heese, Justus; Özcan, Fatih; Heidelmann, Markus; Folke, Jan; Kähler, Kevin; Schlögl, Robert; Behrens, Malte
Abstract: Magnesioferrite (MgFe2 O4 )‐derived Mesoporous spinels of the type MgFeM 3+ O4 with M 3+ =Fe, Al, and Ga obtained upon calcination of hydrotalcite‐like compounds were investigated in the ammonia decomposition reaction at 1 bar and the synthesis of ammonia at 90 bar. The corresponding precursors were synthesized by co‐precipitation at 50 °C and constant pH of 10.5. N2 physisorption, PXRD, HR‐TEM, H2 ‐TPR, and NH3 ‐TPD were applied in order to obtain information about the textural, (micro‐)structural, solid‐state kinetics in reducing atmosphere, and adsorption properties of the samples. While phase‐pure layered double hydroxides (LDHs) were obtained for Al and Ga, magnesioferrite as the desired oxide phase and a low fraction of magnetite were formed besides the targeted precursor phase during co‐precipitation in the presence of Fe 2+ and Fe 3+ species. Reduction of the binary and ternary magnesioferrites occurs via two consecutive reactions. Only the second stage is shifted towards higher temperatures after incorporation of Al and Ga. The latter element boosts the catalytic decomposition of ammonia, yielding a 2‐fold and 5‐fold higher conversion at 500 °C compared to the samples containing Fe 3+ and Al 3+ species, respectively. In situ XRD measurements showed that this unprecedented promotional effect is related to the generation of (Fe, Ga)Fe3 N. This phase, however, is detrimental for the synthesis of ammonia at elevated pressures in which the binary system outperforms the ternary spinels, yielding 30 % of the activity obtained with a highly promoted Fe‐based industrial catalyst. Abstract : The desired oxide phase : Magnesioferrites were investigated in the ammonia decomposition at 1 bar and the synthesis of ammonia at 90 bar. Ga‐doping boosted the decomposition activity due to the formation of GaFe3 N. In contrast, MgFe2 O4 achieved 30 % of the activity obtained for an industrial catalyst in the ammonia synthesis.